Online Abuse of Feminists as An Emerging form of Violence Against Women and Girls - Lewis, Ruth (The British journal of criminology, 2017)
Abuse directed at visible and audible women demonstrates that cyberspace, once heralded as a new, democratic, public sphere, suffers similar gender inequalities as the offline world. This paper reports findings from a national UK study about experiences of online abuse among women who debate feminist politics. It argues that online abuse is most usefully conceived as a form of abuse or violence against women and girls, rather than as a form of communication. It examines the experiences of those receiving online abuse, thereby making a valuable contribution to existing research which tends to focus on analysis of the communications themselves.